PEMBERDAYAAN KELOMPOK TANI MAKMUR DALAM PENINGKATAN PRODUKSI PERTANIAN DI DESA CISADAP KABUPATEN CIAMIS - Andini; Aceng Nursobah; Azka Ziyadul Wafa; Fazar Ari Angga; Ilham Mawardi; Ibah Muhammad Misbahudin; Julian Lutfi Firdaus; Muhammad Aditya Ramadhani A; Yoga Gustiadi; Ii Sujai (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Cisadap village, which is located in Ciamis sub-district, Ciamis district, has a very large rice field area and the majority of the people are farmers. Cisadap Village consists of six hamlets with 6 farmer groups in each hamlet. This research aims to evaluate the effectiveness of empowering farmer groups in increasing agricultural production in Cisadap Village. The empowerment program implemented includes technical training, agricultural counseling, as well as providing tools and materials needed for modern agricultural practices. The research method used is a qualitative approach with interviews and observation as data collection techniques. The research results show that the active participation of farmer group members in training and use of agricultural technology has had a positive impact on increasing production yields. In addition, increased managerial skills and access to resources support the success of this program. These findings indicate that empowerment of farmer groups, if carried out comprehensively and sustainably, can significantly increase agricultural productivity at the village level. This study provides recommendations for implementing similar models in other regions to support food security and farmer welfare.